Pendiversifikasian Sayur Lilin Dalam Rangka Meningkatkan Kesejahteraan Kelompok Usaha Di Desa Lauwon Kecamatan Luwuk Timur Kabupaten Banggai Provinsi Sulawesi Tengah - Ramadhani Chaniago (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
The majority of the residents of Lauwon Village are farmers, who areengaged in agriculture and plantations. It can be seen that the geographical situationis in the form of a plateau with a height of Â± 157 m above sea level. Rainfall in LauwonVillage averages Â± 221 mm / year which is suitable for vegetable candles. Many of thepotential natural resources owned by Lauwon Village are vegetable candles which arequite abundant so that they can be processed into a number of products such as sticks,abon and vegetable candle crackers. The solution that gets priority to be carried out inthis activity is the Development of Counseling and Training Development, namelytechnical training covering; processing wax vegetable sticks, wax crackers andvegetable shredded candles along with packaging and labeling. Non-technical trainingwhich includes; institutional strengthening of partner groups through groupmanagement functions and group financial bookkeeping training. By conductingtraining in making crackers, sticks and shredded vegetables, candles will providebenefits to the community, especially for the wax women group in Lauwon Village, EastLuwuk Subdistrict, Banggai Regency, Central Sulawesi, especially in diversifying theirlocal commodities to be economically valuable and competitive with other foodproducts. In addition, this activity also provides information, knowledge and skills tothe community so that they can innovate in producing agricultural products that canincrease family value added so that the community becomes prosperous.